2017
DOI: 10.3892/or.2017.5520
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of intestinal myofibroblasts by KRas-mutated colorectal cancer cells through heparin-binding epidermal growth factor-like growth factor

Abstract: In colorectal cancer, gain-of-function mutations in KRas play a critical role in malignant transformation. Tumor growth in colorectal cancer is known to be promoted by the intestinal myofibroblasts (IMFs) that localize adjacent to the cancer cells, but the mechanisms of interaction between KRas-mutated cancer cells and the myofibroblasts remain unclear. Here, we investigated the effects of KRas-mutated cells on the behavior of myofibroblasts by using mouse primary IMFs and cells of an IMF cell line (LmcMF) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…For HBEGF, a pivotal role in cancer progression has been proposed in various cancers, including cervical, breast, and gastric cancers [ 20 - 23 ]. In CRC, Kawasaki et al [ 24 ] suggested that HBEGF has roles in CRC progression through the recruitment of intestinal myofibroblasts. In our cohort, although HBEGF expression is commonly detected in CRC, we were unable to determine a significant correlation with various clinicopathologic factors except for tumor differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…For HBEGF, a pivotal role in cancer progression has been proposed in various cancers, including cervical, breast, and gastric cancers [ 20 - 23 ]. In CRC, Kawasaki et al [ 24 ] suggested that HBEGF has roles in CRC progression through the recruitment of intestinal myofibroblasts. In our cohort, although HBEGF expression is commonly detected in CRC, we were unable to determine a significant correlation with various clinicopathologic factors except for tumor differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that the conditioned medium of KRASV12overexpressing colorectal cells strongly increased migration of intestinal fibroblasts without affecting their proliferation rate and their differentiation status. The observed effect was found to be mediated by the heparin-binding EGF-like growth factor (HB-EGF) upregulated by KRAS-mutated cells and activation of HB-EGF receptors, and ERK 1/2 and JNK signals in fibroblasts (70).…”
Section: Modulation Of the Properties Of Cancer-associated Fibroblasts By Mutant Kras Cancer Cellsmentioning
confidence: 99%
“…The IC50 for ERK1 = 0.14 μM and for ERK2 = 0.31 μM. FR180204 attenuates mesothelioma cell proliferation [ 71 ], decreases cell viability colorectal cancer cell lines [ 72 ], decreases cell proliferation and increases apoptosis in colorectal cancer cells in combination with AKT inhibitor API-1 [ 73 ], and inhibits intestinal myofibroblast migration induced by KRAS-mutated colorectal cancer cells [ 74 ]. This inhibitor is also used in arthritis research [ 75 ].…”
Section: Map Kinase Inhibitors In Cancer Researchmentioning
confidence: 99%